Natriuretic peptides and cardiac hs-troponins as surrogates of cardiomyocyte stress: clinical value in hypertrophic cardiomyopathy? : editorial - Giannitsis, Evangelos; Frey, Norbert; Katus, Hugo (European heart journal, 2024)
This editorial refers to ‘Cardiac biomarkers and effects of aficamten in obstructive hypertrophic cardiomyopathy: the SEQUOIA-HCM trial’, by C. J. Coats et al., https://doi.org/10.1093/eurheartj/ehae590.The availability of the cardio-specific biomarkers NT-proBNP and cardiac troponins (cTn) as surrogates of cardiomyocyte structure and function has changed the practice of cardiology. Cardiac troponins are by now not only the preferred marker for the diagnosis of acute myocardial infarction but also for the detection of myocardial cell injury of any cause.1 Secreted natriuretic peptides (NP) best reflect activation of pro-hypertrophic pathways due to increased wall stress and their blood levels thus serve as diagnostic surrogates of congestive heart failure in the guidelines.2 With the advent of high sensitivity cTn assays only 20 years ago,3 it became apparent that elevated cTn blood levels—and even measurable blood levels in the normal range—are associated with cardiovascular remodelling processes and mortality.4 Likewise, the blood levels and delta changes of the analytically robust NT-proBNP marker are not only associated with functional indexes of enhanced cardiac wall stress but also with a patient’s exercise capacity and cardio-vascular outcomes.2